The Effect of Nostalgia Emotion to Brand Trust and Brand Attachment towards Repurchase Intention - et.al, Ayu Nur Hidayati (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A music concert or live music performance is an event that can give more experience to their audiences than just listening to music and this makes people go to their favorite musician’s concert several times. This study has an objective to analyze the effect of nostalgia emotion to brand trust and brand attachment towards repurchase intentions by adding the repurchase intention from the previous studies as a new variable and applying it to the music industry, especially in the live music performance sector. The data used for this study were collected from 120 respondents who have watched music concerts or live music performances in Jakarta through an online survey and analyzed it by using SmartPLS in structural equation modeling (PLS-SEM). This study provides more understanding of the connection between each variable in the chosen industry and indicates that nostalgia emotion of a person can affect their brand trust and brand attachment towards their repurchase intention as the results.